2019
DOI: 10.1007/s11524-019-00372-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Outlet Clusters and Population Disparities

Abstract: Alcohol outlet clusters are an important social determinant of health in cities, but little is known about the populations exposed to them. If outlets cluster in neighborhoods comprised of specific racial/ethnic or economic groups, then they may function as a root cause of urban health disparities. This study used 2016 liquor license data (n = 1204) from Baltimore City, Maryland, and demographic data from the American Community Survey. We defined alcohol outlet clusters by combining SaTScan moving window metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…The CDC collects health outcome data on the state level, categorizing the data with Federal Information Processing (FIPS) two-digit codes that each identify a United States state or territory. We retrieved 12 outcome indicators: (1) obesity and (2) overweight status of adults (percentage of adults aged 18 years or older with an obesity and overweight classification, respectively, in 2017), (3) obesity and (4) overweight status of adolescents (percentage of teenagers in grades 9-12 with an obesity and overweight classification, respectively, in 2017), (5) diabetes in adults (prevalence of adults aged 18 years or older with diagnosed diabetes in 2016), ( 6) aerobic physical activity in adults (percentage of adults who had at least 150 minutes of moderately intense aerobic physical activity, or 75 minutes of vigorously intense aerobic activity, or an equivalent combination per week in 2017), (7) daily physical activity in adolescents (percentage of teenagers in grades 9-12 who had one hour or more of moderate to vigorous physical activity on a daily basis in 2017), (8) premature mortality (cases of premature mortality per 100,000 among adults aged 45 to 64 years), (9) diabetes mortality (cases of diabetes-related mortality per 100,000 in 2014), (10) cardiovascular disease mortality (cases of cardiovascular disease-related mortality per 100,000 in 2014), (11) park access (percent of USA population living within 1/2 mile of a park in 2015), and (12) youth recreational access (percent of youth with playgrounds, community centers, or sidewalks in their neighborhood in 2016). The classification of overweight and obesity is based on body mass index (BMI), with overweight classified between 25 and 30, and 30 or greater classified as obese.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDC collects health outcome data on the state level, categorizing the data with Federal Information Processing (FIPS) two-digit codes that each identify a United States state or territory. We retrieved 12 outcome indicators: (1) obesity and (2) overweight status of adults (percentage of adults aged 18 years or older with an obesity and overweight classification, respectively, in 2017), (3) obesity and (4) overweight status of adolescents (percentage of teenagers in grades 9-12 with an obesity and overweight classification, respectively, in 2017), (5) diabetes in adults (prevalence of adults aged 18 years or older with diagnosed diabetes in 2016), ( 6) aerobic physical activity in adults (percentage of adults who had at least 150 minutes of moderately intense aerobic physical activity, or 75 minutes of vigorously intense aerobic activity, or an equivalent combination per week in 2017), (7) daily physical activity in adolescents (percentage of teenagers in grades 9-12 who had one hour or more of moderate to vigorous physical activity on a daily basis in 2017), (8) premature mortality (cases of premature mortality per 100,000 among adults aged 45 to 64 years), (9) diabetes mortality (cases of diabetes-related mortality per 100,000 in 2014), (10) cardiovascular disease mortality (cases of cardiovascular disease-related mortality per 100,000 in 2014), (11) park access (percent of USA population living within 1/2 mile of a park in 2015), and (12) youth recreational access (percent of youth with playgrounds, community centers, or sidewalks in their neighborhood in 2016). The classification of overweight and obesity is based on body mass index (BMI), with overweight classified between 25 and 30, and 30 or greater classified as obese.…”
Section: Methodsmentioning
confidence: 99%
“…Discriminatory policies such as redlining, a real estate practice discriminating against money or credit borrowers from certain areas with poverty in the United States, has resulted in uneven urban development, creating distinct geographic areas that still face systemic disadvantages [8]. Many of these neighborhoods have built environment features that are detrimental to residents' long-term health, such as more alcohol outlets [9] and fast food restaurants, fewer recreational facilities [10], and higher levels of intra-urban heat [11].…”
Section: Introductionmentioning
confidence: 99%
“…Not merely of historical interest, such questions are highly relevant to current policy debates about potential remedies ( 1 , 2 , 11 , 12 ). To date, 4 published studies, each focused on single cities, have documented associations between historical redlining and health outcomes: tuberculosis incidence in 1951 in Austin, Texas ( 13 ); firearm injury rates in 2013–2014 in Philadelphia, Pennsylvania ( 14 ); self-rated health in 2008–2013 in Detroit, Michigan ( 15 ); and alcohol outlet clusters in 2016 in Baltimore, Maryland ( 16 ), in addition to 2 conference abstracts pertaining to asthma ( 17 , 18 ).…”
Section: Abbreviationsmentioning
confidence: 99%
“…HOLC ‘redlining’ has been associated with pre-term birth ( Krieger, Van Wye, et al, 2020 ), later stage cancer diagnosis ( Krieger, Wright, et al, 2020 ), higher rates of emergency department visits for asthma ( Nardone et al, 2020 ), and poorer self-reported health ( McClure et al, 2019 ). HOLC ‘redlining’ has also been associated with neighborhood determinants of health, including alcohol outlet clusters ( Trangenstein et al, 2020 ), urban violence ( Jacoby et al, 2018 ), less tree canopy and more airborne hazards ( Namin et al, 2020 ), and higher intra-urban heat ( Hoffman et al, 2020 ). McClure et al ( McClure et al, 2019 ) is the only other study that we are aware of that has evaluated HOLC ‘redlining’ in relation to current housing instability (i.e., post Great Recession foreclosure rates) and health.…”
Section: Introductionmentioning
confidence: 99%